Mechanics - Datta, Sunil (PHI Learning, 2010)
Intended as a text for the undergraduate students of Mathematics, this book provides an in-depth analysis on the theoretical and practical applications of Mechanics. The concepts and the theories expressed are treated mathematically with a simple yet logical approach. The book is written to augment the understanding of the students of this discipline. The book comprises the topics like Newton?s Laws of motion; concepts of work, energy and impulse; and relative motion. It effectively elucidates the principles of forces in three dimensions, equilibrium of strings, and rectilinear motion like simple harmonic motion. The book explains the motion of the earth, the moon, the stars and other heavenly bodies with the help of principles of mechanics. The topics like motion of a rocket and motion of an artificial satellite are also covered in detail so that the students are introduced to the contemporary subjects like space dynamics. All the chapters are well-supported with figures and illustrative examples. The chapter-end exercises help to judge students? comprehension on the subject.